2010
DOI: 10.1039/c0cc01887b
|View full text |Cite
|
Sign up to set email alerts
|

Potential photoactivated metallopharmaceuticals: from active molecules to supported drugs

Abstract: Apart from cisplatin and some derivatives successful metallopharmaceuticals are still scarce in antitumour therapy. Although novel metal complexes have been investigated in preclinical settings several promising compounds failed in different phases. With the rise of new anticancer compounds new activation strategies have also evolved. Photochemical activation is one of the most important concepts as it uses pro-drugs whose activity can be triggered by light. This strategy offers the possibility to control the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
96
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(105 citation statements)
references
References 102 publications
1
96
0
8
Order By: Relevance
“…Thus, our strategy adds a new brick to the recently proposed approach of metal-based drug activation by light irradiation. [33][34][35]38] Very demonstrative work from Sadler et al [36] showed that irradiation at 420 nm of a platinum(IV) complex can make it one order of magnitude more cytotoxic than in the dark. Like in PDT, the wavelength of the light used to irradiate the tumor should indeed be high enough in the visible (or NIR) region to allow deep and harmless penetration of the photons in living tissues.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, our strategy adds a new brick to the recently proposed approach of metal-based drug activation by light irradiation. [33][34][35]38] Very demonstrative work from Sadler et al [36] showed that irradiation at 420 nm of a platinum(IV) complex can make it one order of magnitude more cytotoxic than in the dark. Like in PDT, the wavelength of the light used to irradiate the tumor should indeed be high enough in the visible (or NIR) region to allow deep and harmless penetration of the photons in living tissues.…”
mentioning
confidence: 97%
“…The use of light to cure cancer, which has notably led to the clinical development of photodynamic therapy, [30][31][32] has also been proposed as an interesting development in metal-based anticancer drug research, in which the presence of oxygen is not required. [33][34][35][36][37][38] To investigate this concept, we selected two monodentate thioether ligands of natural origin: N-acetyl-l-methionine and d-biotin, and synthesized their ruthenium complexes…”
mentioning
confidence: 99%
“…[18] This strategy was not successful in the case of the open complexes; they were synthesized in two steps. [21] First the dichlorido-bridged dimer was obtained by reaction of the desired ligand (7,10) All the intermediates and the target complexes were characterized by IR and NMR ( 1 H and 13 C) spectroscopy and mass spectrometry, and the characteristic data are reported in the Experimental Section and in the Supporting Information. Complexes 1-4 show only one set of NMR spectroscopic signals for the three phenylpyridine ligands, which proves that the threefold symmetry expected for fac complexes is maintained.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, hexafluoroisopropanol (HFIP) was proposed as a suitable candidate for the preparation of polymer nanoparticles via the emulsion-solvent evaporation method. It also has the ability to be a good solvent for metallopharmaceuticals that need to be embedded in a carrier material to be delivered in the body [98]. A ruthenium nitrosyl complex designed for phototherapy that is polar but not soluble in water could be successfully encaspulated in polymer nanoparticles after the evaporation of HFIP from HFIP-in-alkane miniemulsions (Fig.…”
Section: New Emulsionsmentioning
confidence: 99%